Análisis al manejo de las finanzas y su relación con el registro y uso del sistema contable de los pequeños y medianos negocios de la parroquia san camilo de la ciudad de Quevedo, periodo 2012 - Mera Esquivel, Juliana Alexandra (2013)
This research project contains information relevant to the relationship between the use of registration and accounting control and its influence on the economic development of small businesses in the parish San Camilo Quevedo City, in 2012. Analyzed so how is the financial management in small businesses, how to record the daily business activities and under what accounting system. So who identified the greatest impact commercial activity within the parish, accounting procedures, beyond the identification of business had a stable economy. Thus, for this purpose we collected information about the system for accounting and tax and profit determination system. Using inductive and descriptive methodology and supported as primary sources and secondary survey, availing of books, and websites are able to check the relationship between the use of the registry variables and accounting and financial control with her company's economic situation , based on parameters such as training, technology, and investment returns. I mean it was identified that a possible relationship in the registration and use of accounting and financial control and the economic situation of the company.